Novel synthesis of 0D, 1D and 2D nano-CsxWO3 and their tunable optical-thermal response performance. Issue 30 (9th July 2020) - Liu, Guanghui; Kong, Fandong; Xu, Ju; Li, Ruixing
Abstract : 0D, 1D and 2D nano-Cs0.3 WO3 were successfully synthesized in a controllable way, and their photoresponse properties were systematically investigated. Abstract : The synthesis of shape-controlled nanoparticles has attracted wide attention in recent years due to their tunable properties along with various morphologies. Cs x WO3 is a great candidate for application in solar filters based on its high transmittance in the visible region and excellent shielding performance in the near-infrared (NIR) region. However, the relationship between NIR absorption performance and different shaped Cs x WO3 particles has been rarely reported. In this paper, two-dimensional (2D) Cs0.3 WO3 nanosheets, one-dimensional (1D) Cs0.3 WO3 nanofibers and zero-dimensional (0D) Cs0.3 WO3 nanoparticles were successfully synthesized via a simple hydrothermal approach, and the related photoresponse properties were also investigated. The results show that the 2D nanosheets present much stronger absorption in the wavelength range of 300–20 000 nm as compared to the 1D nanofibers and 0D nanoparticles. Under 10 s of continual irradiation by a 50 W halogen lamp, the peak temperature of the 1D nanofibers and 0D nanoparticles increased from 20 °C to 73.2 °C and 63.8 °C, which are only 53.2 °C and 43.8 °C temperature gains, respectively. For the 2D nanosheets the peak temperature reached to 88.5 °C, which is about 68.5 °C temperature gain, almost 56% and 29% higher than that of the 0D nanoparticles and 1D nanofibers, respectively. The highest adiabatic temperature difference between the blank quartz glass and 2D Cs0.3 WO3 nanosheets coated on the quartz glass was 9.2 °C. The photothermal conversion efficiency of the 2D, 1D and 0D samples was about 43.2%, 27.6% and 24.4%, respectively. These results indicate that the 2D Cs0.3 WO3 sample is an effective NIR absorption and photothermal conversion material that can be used for NIR shielding, and also has great potential in biomedical applications.